Variability of Mercury Concentrations Across Species, Brand, and Tissue Type in Processed Commercial Seafood Products - Kylie D. Rock; Shriya Bhoothapuri; Emanuel Lassiter; Leah Segedie; Scott M. Belcher (Toxics, 2025)
Mercury (Hg) is a global health concern due to its prevalence, persistence, and toxicity. Numerous studies have assessed Hg concentrations in seafood, but variability in reported concentrations highlights the need for continued monitoring and stricter regulations. We measured total Hg (tHg) in 148 pre-processed, packaged seafood products purchased in Raleigh, North Carolina, using thermal decomposition–gold amalgamation atomic absorption spectrophotometry. Products were grouped into three categories based on trophic ecology and physiology: (1) tuna, (2) other bony fish, and (3) shellfish and squid. Among tuna, albacore had the highest average tHg (396.4 ng/g ± 172.1), while yellowfin had the lowest (68.3 ng/g ± 64.7). Herring (54.0 ng/g ± 23.2) and crab (78.2 ng/g ± 24.1) had the highest concentrations in the other two groups. One can of albacore exceeded the FDA action level of 1 part per million (1.3 ppm or 1300 ng/g). Brand differences were significant for both albacore and light tuna, with Brand 1 consistently showing higher Hg levels. Comparisons to FDA data (1990–2012) suggest Hg concentrations in tuna have remained stable over the past two decades. This study underscores the variability of Hg concentrations across species and brands and the need for continued monitoring to protect consumers.